Comparison of Leiomyoma of Modern Medicine and Traditional Persian Medicine. (April 2016) - Tansaz, Mojgan; Tajadini, Haleh
Leiomyoma is the most common benign tumor of the pelvic that is associated with reproductive problems such as infertility, frequent abortions, and undesirable prenatal outcomes. High prevalence of leiomyoma and its relation with important gynecological complications, especially during reproductive ages, on the one hand, and high medical expenses and significant complications of common treatments, on the other, made us search traditional Persian medicine texts for a similar disease. In traditional Persian medicine, a condition has been introduced similar to leiomyoma ( Oram-e-rahem ). In this article, by collecting materials from traditional medicine texts on leiomyoma, we aim to provide theories for further studies on this topic, as there is an obvious difference between traditional Persian medicine and modern medicine with regard to leiomyoma. When modern medicine has not found a suitable response to treatment, reviewing of traditional Persian medicine for finding better treatment strategies is wise.